Discovering favorable genes, QTLs, and genotypes as a genetic resource for sesame (Sesamum indicum L.) improvement - Kefale, Habtamu; Wang, Linhai (Frontiers in Genetics, 2022)
Sesame (Sesamum indicum L) is a diploid ancient oilseed crop with high oil content, quality protein, and antioxidant characteristics that is produced in many countries in the World. Genes, QTLs, and genetic resources of sesame have been explored more and are being utilized by sesame research institutions, and growers. The crop has many useful traits identified by many researchers and is now available on different platforms. Gene, genotype, QTL, and other genetic diversity data of sesame were collected and stored in more than nine genomic data, and five sesame crop markers databases become available online. However, the phenotypic and genotypic variability which would have a great contribution to sesame improvements are limited and not yet accessible. This comprehensive review covered more than 85 original published research papers and scientifically incorporated the results. Based on this, the candidate genes, genotypes, and QTLs of significantly important traits of sesame were identified and presented. Genetic resources related to grain yield and yield component traits, oil content, and quality, drought tolerance, salt tolerance, waterlogging resistance, disease resistance, mineral nutrient, capsule shattering resistance, and other agronomic important traits of sesame were studied. Numerous candidate genotypes, genes, QTLs, and alleles associated with those traits were collected and also discovered. Besides these, chromosome regions and linkage groups, and maps associated with best traits, and candidate genes were also included. Therefore, all the variability found and presented in this paper and sesame genetic information would be very helpful for further sesame improvement.